The stress-strain state of deformed NaCI type single crystals with the sample height smaller than the base side - Boyarintsev, A.Yu.; Gektin, A.V.; Shlyakhturov, V.V. (Functional Materials, 2006)
A real modelling of the mass transfer process in a crystal by visualization of the crystal material motion under deformatioin using markers as well as structure studied have revealed inhomogeneity in the stress fields and in the crystal dislocation structure. Four crystal regions have been distinguished differing in the dislocation structures and the dislocation interaction mechanisms. For each region, the structure evolution has been studied and the structure state diagram has been constructed as a function of the prestrainin rate.